RESPONSE OF ORNAMENTAL GRASSES CULTIVATED UNDER SALINITY STRESS - Monika Henschke (Acta Scientiarum Polonorum: Hortorum Cultus, 2017)
Particularly adverse growing conditions are found in urban green areas, where apart from salinity stress plants are exposed to drought stress. For this reason the aim of this study was to determine the effects of negative action and enhanced resistance to substrate salinity caused by increasing doses of NaCl in cultiva-tion of ornamental grasses Koeleria glauca (Spreng.) DC., Sesleria caerulea (L.) Ard. and Sorghastrum nutans (L.) Nash. Recorded results will provide a contribution to a preliminary classification of analysed grass species in terms of their tolerance to substrate salinity. Sesleria caerulea and S. nutans may be considered to be halophytes, since they tolerate substrate salinity caused by a dose of 30 g NaCl·dm-3, losing max. 50% fresh matter of the aboveground parts. At this salinity level neither RWC nor total N content changed in leaves of these grasses in comparison to those of plants not watered with saline solution. It was shown that contents of K+ and Ca2+ in leaves of  S. nutans increased under the influence of salinity. Koeleria glauca may be considered a salt-tolerant glycophyte, since a 50% loss of fresh matter of the aboveground parts in this grass was observed at salinity caused by the dose of 10 g NaCl·dm-3, while it also accumulated much more Na+ and Cl- in leaves than the above-mentioned species.